Choosing to learn outside the classroom: Rural South African students' motivation for and benefits of participating in voluntary international virtual exchanges - Diana Breshears; Rentia du Plessis (University of Johannesburg, 2024)
In recent years, universities have adopted virtual exchange programmes to promote intercultural competencies, language acquisition, and global citizenship among students. Virtual exchange is praised as a way to provide international experiences to students who do not have the means to study abroad. Current literature on virtual exchange programmes largely focuses on Western experiences, with little attention to the developing countries that participate in these programmes. The purpose of this study is to explore rural South African students' motivations for participation and perceptions of their experiences in their virtual exchange with a midwestern university in the United States of America (USA). 47 students at the University of the Free State's (UFS) Qwaqwa campus took part in four virtual online connections over the course of two months. Unlike most virtual exchange programmes represented in extant research, students participated in the programme voluntarily rather than as part of their prescriptive coursework. Through a focus group interview with 16 of the students at the conclusion of the interactions, we explored their motivations for taking part in the programme, as well as their perceived benefits of participation. Students were overwhelmingly positive about their experience and identified three types of advantages for participation: building relationships, building knowledge, and professional development.